Jam from passion fruit peel / Muhammad Alif Najmi Kamarul, Mirza Zuhaily Mahadzir and Nur Afiqah Mohd Karim - Kamarul, Muhammad Alif Najmi; Mahadzir, Mirza Zuhaily; Mohd Karim, Nur Afiqah (Faculty of Plantation and Agrotechnology, 2023)
This study was carried out to make an innovation that relate with the post-harvesting process. Passion fruit have many benefit for the health. The pulp become jam to avoid waste from it. passion fruit is considered an underrated fruit in Malaysia as the production has not reached commercial cultivation. he passion fruit as the next important commodity could rejuvenate the economy by disseminating equal benefits for both small and large-scale growers.